Reflections on neurology in the 21st century: about Parkinson's disease - Cosentino, Carlos (2021)
Neurology has undergone a beneficial transformation in the last twenty years thanks to new discoveries resulting from basic and clinical research as well as the accelerated development of a series of related disciplines that make up the socalled neurosciences. The most important advances have been made in the precision of the etiology of many diseases, such as genetic or autoimmune diseases, as well as in the understanding of the biomolecular mechanisms underlying many of them. The case of Parkinson's disease is discussed as a model of neurodegenerative disease and where there have been many advances although still insufficient, and a final comment is made on the future of neurology.